2014
DOI: 10.1155/2014/249584
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dyslipidemia and Management in the Thai Population, National Health Examination Survey IV, 2009

Abstract: This study determined the prevalence and management of dyslipidemia in Thai adults using data from the Thai National Health Examination Survey IV in 2009. Dyslipidemia was defined based on the Third Adult Treatment Panel guidelines. A total of 19,021 adults aged 20 yr and over were included. Mean (SE) levels of total cholesterol, HDL-C, LDL-C, and triglycerides were 206.4 (1.03), 46.9 (0.34), 128.7 (1.09), and 131.4 (2.20) mg/dL, respectively. Prevalence of high LDL-C, low HDL-C, and high triglycerides were 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
72
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 32 publications
7
72
5
2
Order By: Relevance
“…Prevalence of high LDL-C, low HDL-C, and high triglycerides were 29.6%, 47.1%, and 38.6%, respectively. 31 The prevalence of dyslipidemia and hypertriglceridemia among Saudi population was about 40% and 44% respectively. Logistic regression analysis revealed that obesity/overweight, age, diabetes were the most important significant predictors of dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of high LDL-C, low HDL-C, and high triglycerides were 29.6%, 47.1%, and 38.6%, respectively. 31 The prevalence of dyslipidemia and hypertriglceridemia among Saudi population was about 40% and 44% respectively. Logistic regression analysis revealed that obesity/overweight, age, diabetes were the most important significant predictors of dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…6 An earlier study 18 reported no relationship between dyslipidemia treatment and place of residence, but our study demonstrated positive association between dyslipidemia awareness or treatment with urban residence. Similarly, studies in Malaysia and Thailand, 33,34 showed high awareness and treatment levels between raised LDL-C and urban centers.…”
Section: Discussionmentioning
confidence: 87%
“…[9], [10] There are a variety of factors that contribute to the prevalence of dyslipidaemia, including geographic location, social and economic status, age, gender and the impact of these factors has been well studied. [11], [12], [13], [14], [15] Cholesterol and lipoproteins levels increase with age in both genders, [16], [17] but the more pronounced increase has been reported in females than in males. [9] The purpose of the study is to find the lipid abnormalities in type 2 Diabetes Mellitus patients…”
Section: Introductionmentioning
confidence: 96%